Multifunctional fabric finishing liquid and application thereof in fabric preparation
By developing multifunctional fabric finishing liquid, using components such as microcapsule powder and resin emulsion to integrate multiple functions, the existing fabric finishing additives have been solved, and the multifunctional finishing and performance improvement of the fabric has been achieved.
Patent Information
- Application Number
- CN202411945862.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
The existing fabric finishing additives have a single function, poor compatibility after integration of multiple additives, complex process, and high energy and material consumption.
Develop a multifunctional fabric finishing solution that integrates six functions: antibacterial, anti-mold, anti-ultraviolet, negative ion release, far-infrared radiation and deodorization by combining microcapsule powder, resin emulsion and water, including micro-scale diatomaceous earth and nano-hybrid powder.
It realizes multi-functional finishing of fabrics, simplifies the process flow, reduces energy consumption and material consumption, and improves the overall performance of fabrics.
Smart Images

Figure CN119843493A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fabric finishing, and in particular relates to a multifunctional fabric finishing liquid and application thereof in fabric preparation. Background Art
[0002] Fabric finishing auxiliaries are chemicals used to improve the performance and appearance of fabrics during textile processing. They can be divided into many types according to enhancing or giving special functions to fabrics, such as softness, wrinkle resistance, waterproofness, fire resistance, antibacterial, UV protection, etc., including softeners, anti-wrinkle agents, waterproof and oil-proof agents, flame retardants, antibacterial agents, UV protection agents, etc.
[0003] Chinese patent CN117468231A discloses an anti-ultraviolet finishing agent for fabrics. The anti-ultraviolet finishing agent for fabrics is prepared from the residue of Ligusticum chuanxiong by a method of high-temperature impregnation with sodium hydroxide. The anti-ultraviolet finishing agent is then used to finish silk fabrics to obtain a silk fabric with an anti-ultraviolet effect.
[0004] Chinese patent CN109338709A discloses an antibacterial finishing agent for fabrics, comprising, by mass percentage: 1-2.5% of the active nano zinc oxide, 20%-32% of the triple-proof finishing agent HS1100, 20%-32% of the antibacterial finishing agent ATB9800, 5%-10% of allyl glycidyl ether, 3%-6% of an initiator and water, which prolongs the antibacterial properties of the fabrics.
[0005] Chinese patent CN116289193A discloses an oil-wax elastic finishing agent for cotton and linen fabrics, which includes semi-refined paraffin wax, refined castor oil, non-ionic film, non-ionic surfactant, amino and epoxy modified high molar mass self-crosslinking polyorganosiloxane emulsion and non-ionic aqueous polyurethane emulsion. The oil-wax component in the emulsion can be evenly adsorbed on the fabric, making the surface of the fabric show a light and delicate oil-wax feel.
[0006] Although the above finishing auxiliaries can significantly improve the fabric's UV resistance, antibacterial properties and feel, they also have the following disadvantages:
[0007] (1) Relatively single function: Many finishing auxiliaries have only one specific function, such as antibacterial and anti-ultraviolet. If you want to achieve multiple effects, you need to use multiple auxiliaries for multiple treatments, which increases the complexity of the process.
[0008] (2) Incompatibility of performance after integrating multiple functions on the same fabric: Different finishing auxiliaries may have conflicting chemical properties. When multiple auxiliaries are used together, they may cause mutual reactions, thereby reducing their respective efficacy or even completely failing.
[0009] (3) High risk of production process failure: Due to the existence of multi-step processing and multi-step drying processes, as well as the potential incompatibility between different auxiliaries, the entire finishing process has a high risk of failure. Any error in any step may result in the final product not meeting the quality standards.
[0010] (4) High energy and material consumption: Each treatment requires additional energy to heat and dry the fabric, which increases energy costs. At the same time, repeated treatments will also cause more material loss and waste. Summary of the invention
[0011] The purpose of the present invention is to provide a multifunctional fabric finishing liquid and its application in fabric preparation, so as to solve the problems that the above-mentioned finishing auxiliaries have relatively single functions, multiple auxiliaries integrated on the same fabric have poor compatibility and the fabric finishing process is relatively complicated.
[0012] In order to achieve the above object, the present invention provides the following technical solutions:
[0013] The first aspect of the present invention provides a multifunctional fabric finishing liquid, which comprises, by mass fraction, 5-25% of microcapsule powder, 5-30% of resin emulsion and the remainder of water; wherein the microcapsule powder comprises micron-grade diatomaceous earth and nano-hybrid powder, the mass ratio of the micron-grade diatomaceous earth to the nano-hybrid powder is (1-3):(1-3), and the nano-hybrid powder comprises, by mass fraction, 1-5 parts of water-based nano-titanium dioxide, 1-5 parts of nano-zinc oxide, 1-5 parts of nano-aluminum oxide, 1-5 parts of nano-lanthanum oxide, 0.1-1.5 parts of nano-silicon dioxide, 0.1-1.5 parts of Guanyin clay nano-powder and 1-5 parts of tourmaline nano-powder.
[0014] In view of the problem that the fabric finishing step in the prior art brings a relatively single function to the fabric, the present invention combines multiple raw materials and integrates multiple functions together, so that the treated fabric has six functions, and obtains a multifunctional fabric. In the present invention, it specifically includes antibacterial, mildew-proof, UV-proof, negative ion release, far-infrared radiation and deodorization. Wherein, by adding water-based nano titanium dioxide (TiO2) and nano zinc oxide (ZnO), these materials have good photocatalytic activity, can produce free radicals under light, destroy bacteria and mold cell walls, thereby achieving efficient antibacterial and mildew-proof effects. Nano titanium dioxide and nano zinc oxide can also absorb and reflect ultraviolet rays, provide UV protection function for fabrics, and protect wearers from ultraviolet damage. Tourmaline nano powder is a natural mineral that can release negative ions under certain conditions, improve environmental air quality, and increase wearing comfort. Diatomaceous earth and certain nano materials (such as tourmaline) can emit far infrared rays, promote blood circulation, help maintain body temperature and improve body comfort. The porous structure and high specific surface area of diatomaceous earth make it an ideal adsorbent that can effectively remove odor molecules.
[0015] Preferably, the solid content of the resin emulsion is 50-55%, and the water-based modulus is 100-1000 GPa.
[0016] Preferably, the resin emulsion is one or more of polyurethane, polyamide and polyethylene.
[0017] Preferably, the average particle size of the micron-sized diatomaceous earth is 1 to 3 μm, and the pore size is 40 to 800 nm.
[0018] Preferably, the average particle size of water-based nano titanium dioxide is 3 to 10 nm, the average particle size of nano zinc oxide is 20 to 50 nm, the average particle size of nano aluminum oxide is 40 to 100 nm, the average particle size of nano lanthanum oxide is 30 to 80 nm, the average particle size of nano silicon dioxide is 10 to 30 nm, the average particle size of Guanyin clay nano powder is 5 to 10 nm, and the average particle size of tourmaline nano powder is 50 to 150 nm.
[0019] More preferably, the average particle size of aqueous nano-titanium dioxide is 5nm, the average particle size of nano-zinc oxide is 30nm, the average particle size of nano-aluminum oxide is 40-100nm, the average particle size of nano-lanthanum oxide is 50nm, the average particle size of nano-silicon dioxide is 20nm, the average particle size of Guanyin clay nano-powder is 7nm, and the average particle size of tourmaline nano-powder is 100nm.
[0020] Water-based nano-titanium dioxide is a photocatalyst material purchased from Tianxing New Materials Co., Ltd., nano-zinc oxide, nano-aluminum oxide and nano-silicon dioxide are all purchased from Tianxing New Materials Co., Ltd., nano-lanthanum oxide is purchased from Shanghai Naio Nano Technology Co., Ltd., Guanyin clay nano-powder is purchased from Guangdong Senxin Industry and Trade Co., Ltd., and tourmaline nano-powder is purchased from Lingshou County Tuolin Mineral Products Processing Plant.
[0021] A second aspect of the present invention provides a method for preparing a multifunctional fabric finishing liquid, comprising the following steps:
[0022] (1) mixing water-based nano titanium dioxide, nano zinc oxide, nano aluminum oxide, nano lanthanum oxide, nano silicon dioxide, Guanyin clay nano powder and tourmaline nano powder to form a nano hybrid powder, adding the nano hybrid powder into water and stirring to form a homogeneous mixture;
[0023] (2) adding micron-sized diatomaceous earth to the homogeneous mixture and stirring evenly to obtain a mixed suspension, heating the mixed suspension to dehydrate it, and polymerizing the nano-hybrid powder on the surface of the diatomaceous earth to obtain a nano-hybrid coating of diatomaceous earth;
[0024] (3) placing the nano-hybrid coated diatomaceous earth in a clay kiln and cooling it naturally to obtain ceramic diatomaceous earth;
[0025] (4) ultrafinely grinding ceramic diatomaceous earth to obtain microcapsule powder;
[0026] (5) The microcapsule powder, resin emulsion and water are uniformly mixed to form a multifunctional fabric finishing liquid.
[0027] In addition to limiting the composition of the finishing liquid, the present invention also specifically designs a preparation method for the finishing liquid, which can continue to optimize the microstructure between the nano-hybrid powder and diatomite in the subsequent preparation process, and further improve the various properties of the finishing liquid. In step (1), various functional nano materials are mixed in water. By mixing them evenly, synergy can be achieved at the microscopic level. In step (2), diatomite is added to the homogeneous mixture. Since diatomite is a porous mineral with a high specific surface area and adsorption capacity, it can not only be used as a carrier to carry the above-mentioned functional nano materials, but also further enhance the adsorption effect through its internal microporous structure, so that the nano materials can be distributed on a larger surface, thereby improving the effects of various functions. During the heating process, water gradually evaporates, resulting in a decrease in the distance between the nanoparticles, which promotes the interaction between the particles. Due to the high surface energy of the nano material, it tends to form a stable chemical bond or physical adsorption on the surface of the diatomite, thereby forming a uniform nano hybrid coating. This step not only enhances the binding force between the nano material and the diatomite, but also provides a stable structural basis for subsequent calcination. In step (3), the diatomite of the nano-hybrid coating is calcined. Due to the secondary ceramic reaction of the Guanyin clay nanopowder and the diatomite during the high-temperature sintering process, more porosity and specific surface area will be formed, showing a stronger nano-hybrid function. The large specific surface area can enhance the antibacterial and mildew-proof functions. In step (4), the ceramicized diatomite is ultra-finely crushed to form a large number of microcapsule powders. Each microcapsule is a unit for eliminating odor and decomposing organic gas molecules, which increases the deodorizing effect; at the same time, each microcapsule can also form a heat storage and far-infrared high-efficiency emission monomer, which enhances the far-infrared function of the fabric; due to the microporous properties of the microcapsule, multiple reflections and elimination of the incident light are increased, and the light-shielding and UV-proof functions are also enhanced. In addition, a microcapsule powder less than 3 microns is formed. Due to its small average particle size, it can be evenly distributed in the subsequent resin solution. When the fabric is post-finished, a micron-level microcapsule coating is formed on the surface of the fabric fiber, which fully demonstrates the hybrid function of the nano-hybrid microcapsule.
[0028] In step (4) of the present invention, microcapsule powder with a particle size of less than 3 μm is obtained by sieving through a 5000 mesh sieve. The smaller the particle size of the microcapsule, the easier it is to achieve uniform integration and distribution in the aqueous resin, so as to achieve uniform coverage on the surface of textile fibers. Since the pore size of diatomaceous earth is 40 to 800 nm, the pore size will slightly increase after calcination. In order to maintain the effect of the microcapsule, 3 μm is selected as the optimal pore size. The microporous specific surface of each microcapsule accumulates efficient nano-hybrid materials, which can concentrate on reflecting the advantageous effects of nano-hybridization, thereby obtaining efficient microcapsule powder.
[0029] Preferably, in step (1), the mass ratio of the nano-hybrid powder to water is 1:(3-9).
[0030] More preferably, in step (1), the mass ratio of the nano-hybrid powder to water is 1:(3-5).
[0031] Preferably, in step (2), the mixed suspension is heated to dehydrate, and when the mixed suspension loses 70-80% of its water, a wet material is obtained, and the wet material is made into a blank and placed in the room to dry naturally in the shade to form a diatomite blank containing microporous particles, i.e., the diatomite with nano-hybrid coating.
[0032] Preferably, in step (3), the calcination temperature is 1100-1200° C. and the time is 7-8 h;
[0033] In step (4), the average particle size of the microcapsule powder is less than 3 μm.
[0034] The purposes of calcination in the present invention are: 1) during the calcination process of various oxidized nanomaterials, the crystallization between the oxidized nanomaterials on the surface is promoted, thereby significantly improving the bonding strength and durability of the nanomaterials on the surface, and the nanoparticles are more tightly bonded; 2) the organic matter in the diatomaceous earth is decomposed and emptied to form a new microporous structure, thereby increasing the specific surface area of the nanomaterial and gaining the nano hybrid function.
[0035] The calcination step in the present invention is a key step in the preparation method. The mixed calcination of nanomaterials is not just a simple mixing of nanomaterials, but also forms a re-combination of nanomolecules during calcination, forming a nanomolecular cross-linked body on the specific surface of microporous diatomite. Since the calcined diatomite has a larger specific surface area, the properties of the nanomaterials will be enhanced. For example, the characteristics of the hybridization of nano zinc oxide and nano titanium dioxide mainly include the following points:
[0036] 1. Antibacterial performance: Nano titanium dioxide has a photocatalytic function and can kill bacteria for a long time under the action of light. Nano zinc oxide has an antibacterial hole conductive function. The combination of the two can enhance the antibacterial effect.
[0037] 2. Anti-mildew performance: Since both nano titanium dioxide and nano zinc oxide have good antibacterial properties, their hybrid finishing agents also show excellent anti-mildew performance.
[0038] 3. Self-cleaning performance: The photocatalytic effect of nano-titanium dioxide can degrade organic pollutants, thereby giving the hybrid finishing agent self-cleaning properties.
[0039] 4. Far infrared performance: Nano zinc oxide has far infrared reflection properties, which are retained in the hybrid finishing agent and help improve the warmth retention and comfort of the material.
[0040] 5. Negative ion performance: Nano zinc oxide can produce negative ions.
[0041] 6. Antistatic performance: Nano zinc oxide has the characteristics of a semiconductor and can provide higher conductivity at room temperature, thus playing an antistatic role.
[0042] 7. Environmental protection: These functions of hybrid finishing agents are achieved through physical and chemical actions, and do not involve the release of harmful substances, so they are very environmentally friendly.
[0043] 8. Washability: The hybridized products can maintain stable performance after multiple washings, showing good washability.
[0044] In summary, nano-hybrid finishing liquid integrates the advantages of each material. It not only has diverse functions, but also enhances the original effects. Its performance is far superior to the properties of the nano-materials of each monomer.
[0045] The third aspect of the present invention provides an application of a multifunctional fabric finishing liquid. In the fabric finishing and shaping process, the multifunctional fabric finishing liquid is applied to the surface of the fabric fiber through the fabric finishing process, and dried at 110-180°C to form a multifunctional fabric with antibacterial, mildew-proof, UV-proof, negative ion, far infrared and deodorizing effects.
[0046] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0047] 1. The present invention combines a variety of functional nanomaterials into a finishing liquid, and the finishing liquid is applied to the fabric preparation process to obtain a multifunctional fabric with six functions of antibacterial, mildew-proof, UV protection, negative ion release, far-infrared radiation and deodorization, thereby expanding the functionality of the fabric.
[0048] 2. The finishing liquid of the present invention integrates multiple functions. When the fabric is post-finished, it can be completed in one step without multiple steps of auxiliary agent treatment and drying treatment. The finishing liquid is easy to use and can save energy and reduce material consumption.
[0049] 3. The present invention not only designs various effects in terms of raw material composition, but also uses the calcination step to further optimize the microstructure of the material during the preparation of the finishing liquid, forming more porosity and specific surface area, and further improving the antibacterial and anti-mildew effects. The present invention also performs ultrafine grinding to obtain microcapsule powder, and each microcapsule powder can be used as a unit to further optimize the deodorizing effect, UV protection effect and far infrared effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the appearance of the fabric prepared in Example 2;
[0051] Figure 2 The test report of the anti-ultraviolet, negative ion, deodorization and antibacterial properties of the fabric prepared in Example 2;
[0052] Figure 3 The test report of the washability, far infrared performance and mildew resistance of the fabric prepared in Example 2;
[0053] Figure 4 These are the results of determining the various properties of the fabric prepared in Example 2. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] This embodiment provides a method for preparing microcapsule powder, which comprises the following steps, calculated by weight:
[0057] (1) 2 parts of water-based nano titanium dioxide, 2 parts of nano zinc oxide, 1 part of nano aluminum oxide, 1 part of rare earth material nano lanthanum oxide, 0.5 parts of nano silicon dioxide, 0.5 parts of harmless Guanyin clay nano powder, and 1 part of tourmaline nano powder are mixed evenly to prepare nano hybrid powder;
[0058] The average particle size of water-based nano titanium dioxide is 5nm, the average particle size of nano zinc oxide is 30nm, the average particle size of nano aluminum oxide is 60nm, the average particle size of nano lanthanum oxide is 50nm, the average particle size of nano silicon dioxide is 20nm, the average particle size of Guanyin clay nano powder is 7nm, and the average particle size of tourmaline nano powder is 100nm.
[0059] Water-based nano-titanium dioxide is a photocatalyst material purchased from Tianxing New Materials Co., Ltd., nano-zinc oxide, nano-aluminum oxide and nano-silicon dioxide are all purchased from Tianxing New Materials Co., Ltd., nano-lanthanum oxide is purchased from Shanghai Naio Nano Technology Co., Ltd., Guanyin clay nano-powder is purchased from Guangdong Senxin Industry and Trade Co., Ltd., and tourmaline nano-powder is purchased from Lingshou County Tuolin Mineral Products Processing Plant.
[0060] (2) adding 2 parts of the prepared nano-hybrid powder to 6 parts of water and stirring to form a homogeneous mixture;
[0061] (3) Add 2 parts of micron-sized diatomite to the homogeneous mixture and stir evenly to obtain a mixed suspension. The micron-sized diatomite has an average particle size of 1 to 3 μm and a pore size of 40 to 800 nm. It is purchased from Guangdong Yufeng Powder Material Co., Ltd. The adsorption performance of diatomite is used to adsorb the nano-hybrid material to form nano-hybrid microcapsules. The mixed suspension is heated to dehydrate. When the mixed suspension loses 75% of its water, a wet material is obtained. The wet material is made into a blank and placed in the room to dry naturally in the shade to form a diatomite blank containing microporous particles. After drying in the shade, it is placed in a ceramic furnace for calcination to form a new hybrid ceramic microporous nano-hybrid composite structure. The calcination temperature is 1100° C. and the time is 8 hours. The powder is crushed again through a 5000 mesh sieve to form a microcapsule powder with six functions of less than 3 μm. The microcapsule powder has antibacterial, anti-mildew, anti-ultraviolet, negative ion generation, far infrared and deodorizing effects.
[0062] Example 2
[0063] This embodiment provides a preparation method and application of a multifunctional fabric finishing liquid, which comprises the following steps by weight:
[0064] (1) Take 1 part of the microcapsule powder prepared in Example 1, 1 part of the resin emulsion, and 8 parts of water and mix them evenly to prepare 40 kg of fabric finishing liquid; wherein the resin emulsion is a flexible resin water-based polyurethane, and the water-based polyurethane is purchased from Shanghai Jinmai, model number JM-5020;
[0065] (2) The fabric finishing liquid is placed in the liquid pool of the setting machine after proofing, and the nylon fabric guide cloth is soaked in the fabric finishing liquid, and is passed through a rolling mill (pressure 0.35MPa), a setting width of 145cm, an oven temperature of 120℃, a speed of 40m / min, and then rolled up to form a nylon fabric product with six functions. The prepared fabric has six functions: antibacterial, mildew-proof, UV-proof, negative ion generation, far infrared and deodorization. The nylon fabric was purchased from Shanghai Yunfei Textile Co., Ltd., and the model was 290T nylon spinning.
[0066] Example 3
[0067] The difference between this embodiment and embodiment 2 is that the type of resin emulsion is different. The resin emulsion used in this embodiment is polyethylene, model 10640, purchased from Jiangsu Yijiu Environmental Protection Technology Co., Ltd.
[0068] This embodiment provides a preparation method and application of a multifunctional fabric finishing liquid, which comprises the following steps by weight:
[0069] (1) Take 1 part of the microcapsule powder prepared in Example 1, 1 part of the resin emulsion, and 8 parts of water and mix them evenly to prepare 40 kg of fabric finishing liquid; wherein the resin emulsion is a flexible resin water-based polyethylene, and the water-based polyethylene is from Jiangsu Yijiu Environmental Protection Technology Co., Ltd., model 10640.
[0070] (2) The fabric finishing liquid is placed in the liquid pool of the setting machine after proofing, and the nylon fabric guide cloth is soaked in the fabric finishing liquid, passed through the rolling mill (pressure 0.35MPa), the width of the setting door is 145cm, the oven temperature is 120℃, the speed is 40m / min, and after drying, it is rolled to form a nylon fabric product with six functions. The nylon fabric was purchased from Shanghai Yunfei Textile Co., Ltd., and the model is 290T nylon spinning.
[0071] Comparative Example 1
[0072] The difference between this comparative example and Example 2 is that the amount of microcapsule powder used is different.
[0073] This comparative example provides a preparation method and application of a multifunctional fabric finishing liquid, which comprises the following steps by weight:
[0074] (1) 0.1 part of the microcapsule powder prepared in Example 1, 0.1 part of the resin emulsion, and 9.8 parts of water were mixed evenly to prepare 40 kg of fabric finishing liquid; wherein the resin emulsion was a flexible resin water-based polyurethane, and the water-based polyurethane was purchased from Shanghai Jinmai, model number JM-5020;
[0075] (2) The fabric finishing liquid is placed in the liquid pool of the setting machine after proofing, and the nylon fabric guide cloth is soaked in the fabric finishing liquid, passed through the rolling mill (pressure 0.35MPa), the width of the setting door is 145cm, the oven temperature is 120℃, the speed is 40m / min, and after drying, it is rolled to form a nylon fabric product with six functions. The nylon fabric was purchased from Shanghai Yunfei Textile Co., Ltd., and the model is 290T nylon spinning.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 3 is that the amount of microcapsule powder used is different.
[0078] This comparative example provides a preparation method and application of a multifunctional fabric finishing liquid, which comprises the following steps by weight:
[0079] (1) Take 0.1 parts of the microcapsule powder prepared in Example 1, 0.1 parts of the resin emulsion, and 9.8 parts of water and mix them evenly to prepare 40 kg of fabric finishing liquid; wherein the resin emulsion is a flexible resin water-based polyethylene, and the water-based polyethylene is from Jiangsu Yijiu Environmental Protection Technology Co., Ltd., model 10640.
[0080] (2) The fabric finishing liquid is placed in the liquid pool of the setting machine after proofing, and the nylon fabric guide cloth is soaked in the fabric finishing liquid, passed through the rolling mill (pressure 0.35MPa), the width of the setting door is 145cm, the oven temperature is 120℃, the speed is 40m / min, and after drying, it is rolled to form a nylon fabric product with six functions. The nylon fabric was purchased from Shanghai Yunfei Textile Co., Ltd., and the model is 290T nylon spinning.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that no calcination operation is performed in step (3), the air-dried diatomaceous earth embryo is directly crushed through a 5000-mesh sieve to form a powder of less than 3 μm, and the powder is applied to the preparation and application of the fabric finishing liquid in Example 2 to obtain a fabric treated by a post-finishing process.
[0083] A preparation method and application of a multifunctional fabric finishing liquid, calculated by weight, comprises the following steps:
[0084] (1) Take 1 part of the uncalcined microcapsule powder prepared in Comparative Example 3, 1 part of the resin emulsion, and 8 parts of water and mix them evenly to prepare 40 kg of fabric finishing liquid; wherein the resin emulsion is a flexible resin water-based polyurethane, and the water-based polyurethane is purchased from Shanghai Jinmai, model number JM-5020;
[0085] (2) The fabric finishing liquid is placed in the liquid pool of the setting machine after proofing, and the nylon fabric guide cloth is soaked in the fabric finishing liquid, passed through the rolling mill (pressure 0.35MPa), the width of the setting door is 145cm, the oven temperature is 120℃, the speed is 40m / min, and after drying, it is rolled to form a nylon fabric product with six functions. The nylon fabric was purchased from Shanghai Yunfei Textile Co., Ltd., and the model is 290T nylon spinning.
[0086] Performance Testing
[0087] The fabrics prepared in the examples and comparative examples were tested for their efficacy, and the test results are shown in the table below.
[0088] Anti-ultraviolet efficacy test: in accordance with GB / T 18830-2009 "Evaluation of UV protection performance of textiles".
[0089] Antibacterial performance test: According to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the test bacteria include Staphylococcus aureus ATCC6538, Escherichia coli 8099, and Candida albicans ATCC10231.
[0090] Washing performance test: Follow the washing regulations in 10.1.2 of GB / T 20944.3-2008, wash 50 times, dry, and then test the antibacterial performance of the fabric again according to the oscillation method of GB / T 20944.3-2008.
[0091] Anti-mildew performance test: According to the GB / T 24346-2009 culture dish method, the test strains include Aspergillus niger ATCC16404, Penicillium funiculosum CGMCC3.3875, Chaetomium globosum ATCC6205, and Trichoderma viride CGMCC3.2941; the anti-mildew performance evaluation criteria are:
[0092] Level 0: No obvious mold growth under a magnifying glass;
[0093] Level 1: Mold growth is sparse or localized, covering less than 10% of the sample surface;
[0094] Level 2: The mold covers less than 30% of the sample surface (10% to 30%);
[0095] Level 3: The coverage area of mold on the sample surface is less than 60% (30% to 60%);
[0096] Level 4: Mold covers 60% or more of the sample surface.
[0097] Far infrared performance test: in accordance with GB / T 30127-2013 "Testing and evaluation of far infrared performance of textiles".
[0098] Negative ion generation test: According to GB / T 30128-2013 "Testing and evaluation of negative ion generation of textiles", the result judgment criteria are as follows:
[0099] Negative ion generation > 1000 / cm 3 , the amount of negative ions generated is higher;
[0100] The amount of negative ions generated is 550 to 1000 / cm 3 , the amount of negative ions generated is moderate;
[0101] Negative ion generation amount <550 / cm 3 , the amount of negative ions generated is low.
[0102] Deodorization efficacy test: in accordance with GB / T 33610.1-2019 "Determination of deodorization performance of textiles Part 1: General rules".
[0103] Table 1 UV protection performance test results
[0104]
[0105] Table 2 Antibacterial performance test results
[0106]
[0107]
[0108] Table 3 50 times washing durability test results Table 4 Anti-mildew performance test results
[0109]
[0110] Table 5 Far infrared performance test results
[0111]
[0112]
[0113] Table 6 Negative ion performance test results
[0114]
[0115] Table 7 Deodorization performance test results
[0116]
[0117] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multifunctional fabric finishing liquid, characterized in that: The multifunctional fabric finishing liquid comprises, by weight, 5-25% of microcapsule powder, 5-30% of resin emulsion and the balance of water; wherein the microcapsule powder comprises micron-grade diatomaceous earth and nano-hybrid powder, the mass ratio of the micron-grade diatomaceous earth to the nano-hybrid powder is (1-3):(1-3), and the nano-hybrid powder comprises, by weight, 1-5 parts of water-based nano-titanium dioxide, 1-5 parts of nano-zinc oxide, 1-5 parts of nano-aluminum oxide, 1-5 parts of nano-lanthanum oxide, 0.1-1.5 parts of nano-silicon dioxide, 0.1-1.5 parts of Guanyin clay nano-powder and 1-5 parts of tourmaline nano-powder.
2. A multifunctional fabric finishing liquid according to claim 1, characterized in that: The solid content of the resin emulsion is 50-55%, and the water-based modulus is 100-1000 GPa.
3. The multifunctional fabric finishing liquid according to claim 1, characterized in that: The resin emulsion is one or more of polyurethane, polyamide and polyethylene.
4. The multifunctional fabric finishing liquid according to claim 1, characterized in that: The average particle size of micron-sized diatomaceous earth is 1 to 3 μm, and the pore size is 40 to 800 nm.
5. The multifunctional fabric finishing liquid according to claim 1, characterized in that: The average particle size of water-based nano titanium dioxide is 3-10nm, the average particle size of nano zinc oxide is 20-50nm, the average particle size of nano aluminum oxide is 40-100nm, the average particle size of nano lanthanum oxide is 30-80nm, the average particle size of nano silicon dioxide is 10-30nm, the average particle size of Guanyin clay nano powder is 5-10nm, and the average particle size of tourmaline nano powder is 50-150nm.
6. A method for preparing a multifunctional fabric finishing liquid according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing water-based nano titanium dioxide, nano zinc oxide, nano aluminum oxide, nano lanthanum oxide, nano silicon dioxide, Guanyin clay nano powder and tourmaline nano powder to form a nano hybrid powder, adding the nano hybrid powder into water and stirring to form a homogeneous mixture; (2) adding micron-sized diatomaceous earth to the homogeneous mixture and stirring evenly to obtain a mixed suspension, heating the mixed suspension to dehydrate it, and polymerizing the nano-hybrid powder on the surface of the diatomaceous earth to obtain a nano-hybrid coating of diatomaceous earth; (3) placing the nano-hybrid coated diatomaceous earth in a clay kiln for calcination, and after natural cooling, obtaining ceramic diatomaceous earth; (4) ultrafinely grinding ceramic diatomaceous earth to obtain microcapsule powder; (5) The microcapsule powder, resin emulsion and water are uniformly mixed to form a multifunctional fabric finishing liquid.
7. The method for preparing a multifunctional fabric finishing liquid according to claim 6, characterized in that: In step (1), the mass ratio of the nano-hybrid powder to water is 1:(3-9).
8. The method for preparing a multifunctional fabric finishing liquid according to claim 6, characterized in that: In step (2), the mixed suspension is heated to dehydrate. When the mixed suspension loses 70-80% of its water, a wet material is obtained. The wet material is made into a blank and placed in the room to dry naturally in the shade to form a diatomite blank containing microporous particles, i.e., the diatomite with nano-hybrid coating.
9. The method for preparing a multifunctional fabric finishing liquid according to claim 6, characterized in that: In step (3), the calcination temperature is 1100-1200° C. and the time is 7-8 hours; In step (4), the average particle size of the microcapsule powder is less than 3 μm.
10. The use of a multifunctional fabric finishing liquid according to any one of claims 1 to 5, characterized in that: In the fabric finishing and shaping process, the multifunctional fabric finishing liquid is applied to the surface of the fabric fiber through the fabric finishing process, and dried at 110-180°C to form a multifunctional fabric with antibacterial, anti-mildew, anti-ultraviolet, negative ion, far infrared and deodorizing effects.
Citation Information
Patent Citations
Antibacterial finishing agent for fabrics and preparation method of antibacterial finishing agent
CN109338709A
Oil-wax-feeling elastic finishing agent for cotton and linen fabrics and preparation method of oil-wax-feeling elastic finishing agent
CN116289193A
Anti-ultraviolet finishing agent for fabric and anti-ultraviolet real silk fabric
CN117468231A
Cited By
Nanometer type multifunctional negative ion material and preparation method thereof
CN121488974A